PENGARUH KINERJA KEUANGAN TERHADAP PROYEKSI KEBANGKRUTAN PADA PERUSAHAAN SUB SEKTOR PERIKANAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009-2016) - Lakonardi Nurraditya; Hari Gursida; Arief Tri Hardiyanto (Universitas Pakuan, 2019)
The purpose of this study is to determine and analyze the effect of financial performance on the projection of bankruptcy in the company of fishery sub-sector. This research was conducted by using secondary data of fishery sub-sector company period 2009-2016. In this study the amount of data taken is 5 companies for 8 years. The data analysis used multiple linear regression with the help of SPSS program. Liquidity there is no significant effect on the projection of bankruptcy. Profitability has no significant effect on bankruptcy projection. Solvency has no significant effect on bankruptcy projection. Activity there is significant influence to bankruptcy projection Together F test results can be known F value is positive marked 81.956 with a significance value of 0.000 0.05 thus this shows that the resulting regression equation is feasible to use, and liquidity factor, profitability , solvency and activity together have a significant positive effect on the projection of bankruptcy at companies listed in the stock exchange indonesia period 2009-2016.